2003
DOI: 10.1182/blood-2002-11-3507
|View full text |Cite
|
Sign up to set email alerts
|

MEK/ERK pathway is aberrantly active in Hodgkin disease: a signaling pathway shared by CD30, CD40, and RANK that regulates cell proliferation and survival

Abstract: The mitogen-activated protein kinase (MAPK) (also called extracellular signal-regulated kinase [ERK]) pathway has been implicated in malignant transformation and in the regulation of cellular growth and proliferation of several tumor types, but its expression and function in Hodgkin disease (HD) are unknown. We report here that the active phosphorylated form of MAPK/ERK is aberrantly expressed in cultured and primary HD cells. Inhibition of the upstream MAPK kinase (also called MEK) by the small molecule UO126… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
164
0
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(182 citation statements)
references
References 54 publications
(58 reference statements)
8
164
0
6
Order By: Relevance
“…The activation of CD30 by CD30L has previously been shown to cause ERK phosphorylation and NF-kB activation in HRS cell lines (29)(30)(31), and, indeed, we observed increased ERK1/2 phosphorylation and increases in the activity of the alternative NF-kB pathway upon lestaurtinib treatment in all analyzed HRS cell lines. TRAIL usually induces apoptosis in tumor cells via the TRAIL-Rassociated DISC.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The activation of CD30 by CD30L has previously been shown to cause ERK phosphorylation and NF-kB activation in HRS cell lines (29)(30)(31), and, indeed, we observed increased ERK1/2 phosphorylation and increases in the activity of the alternative NF-kB pathway upon lestaurtinib treatment in all analyzed HRS cell lines. TRAIL usually induces apoptosis in tumor cells via the TRAIL-Rassociated DISC.…”
Section: Discussionsupporting
confidence: 53%
“…CD30, a cell surface TNF receptor (TNFR) expressed by most HRS cells and HRS cell lines (28), has been shown to activate the MEK/ERK pathway and the classical and alternative NF-kB pathways upon binding of its ligand (29)(30)(31). The observed increases in ERK1/2 phosphorylation upon lestaurtinib treatment are thus most likely due to the CD30L upregulation.…”
Section: Lestaurtinib Activates the Alternative Nf-kb Pathway In Hrs mentioning
confidence: 99%
“…31,32 To analyze whether in MOG-EAE under Epo treatment the activity of MEK determines the expression of Bcl-2 or Bax, we performed Western blot analysis of Bcl-2 as well as Bax immunostaining in animals treated with PD 98059. These experiments revealed that Bcl-2 and Bax levels under Epo application were unaffected by inhibition of MAPK phosphorylation (Figures 3c and 4b).…”
Section: Epo-induced Regulation Of Bcl-2 and Bax Does Not Depend On Pmentioning
confidence: 99%
“…Studies on signaling pathways of HRS cells have implicated deregulated activation of a variety of intercellular proteins (NF-κB, Jak/STATs, Akt/mTOR, Notch-1, and ERK) as well as surface receptors (CD30 and CD40) (Clodi and Younes, 1997;Fiumara et al, 2001;Younes et al, 2003;Zheng et al, 2003), which are highly associated with pro-survival signals. Each of these proteins can be a therapeutic target of selective small molecule inhibitors.…”
Section: Hrs Cellsmentioning
confidence: 99%